Politekhnicheskii institut i voina . Politekhnicheskii institut i voina . Polytechnic Institute and the War . Политехнический институт и война - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Program on students and professors at the Polytechnic Institute in Leningrad who fought at the front of the World War II and worked in Leningrad during the siege. Программа о студентах и профессорах Политехнического Института в Ленинграде, воевавших на фронте Второй молодой войны и трудившихся в Ленинграде во время блокады.